Representasi Prestasi Akademik Pada Mahasiswa Program Studi Pendidikan Ekonomi Yang Aktif Dalam Organisasi Kemahasiswaan Universitas Bhinneka PGRI - Umami, Nailariza; Koiriyah, Henik Yuni; Hastuti, Maria Agatha Sri Widyanti (Universitas Hamzanwadi, 2024)
Students think that being active in organizations can reduce academic achievement so that it causes delays in study and is faced with a dual role as a student who must excel academically and take care of ormawa. This study aims to determine the representation of academic achievement of students who are active in organizations. This research uses descriptive qualitative research methods with data collection techniques through observation, interviews and documentation. The results showed that organizational activeness can increase the Grade Point Average (GPA) as evidenced that almost all award recipients are those who are actively involved in organizations. Organizational activeness can increase motivation, learning achievement as well as existence and self-actualization. Organizational activity can have a positive impact, namely an increased level of self-confidence, fostering leadership, organized time management, critical thinking, honed public speaking and having good relationships. And the strategies carried out by students to maintain academic performance include setting the Pomodoro Technique time, using an urgency matrix and flowchart to make it easier to determine the level of urgency of tasks, and involvement in the Merdeka Learning Campus Merdeka (MBKM) program which can be converted to Semester Credit Units (SKS).